Friction and thickness effect on the progressive forming of hollow pins - simulation and experimental study - Loh, Loong Ee. (2011)
The purpose of this final year project is to investigate the effect of friction and material strip thickness on the progressive forming of micro-hollow pins through simulation and an experimental study. A compression test was conducted to obtain the material property of Copper where the test data was used to calculate the stress-strain statistics which then served as an input in the software Deform2D for the simulation process. The experiment was subsequently carried out on the Schmidt Servo Press and the formed micro-hollow pins were measured for the lengths and characterized through the Hardness and Surface Quality test. The principle conclusion was that an increase in Copper strip thickness corresponded with longer micro-hollow pin. Additionally, micro-hollow pins formed under dry conditions were longer than those formed under lubricated conditions. There was no significant effect of difference in friction factor on the hardness but the surface quality of the micro-hollow pins formed under dry conditions are better than lubricated.